Dolphins - Lever, E. Melanie; Lovett, Kate; Slater, Pat.; Parish, Steve (Milwaukee, WI, 2000)
Text and photographs present the life cycle, habits, and physical characteristics of dolphins.
Keywords: Dolphins; Juvenile literature; Dolphins